The Skills of Female Immigrants to Australia, Canada, and the United States - Heather Antecol; Deborah A. Cobb-Clark; Stephen J. Trejo (Claremont McKenna College, Department of Economics, 2001)
Census data for 1990/91 indicate that Australian and Canadian female immigrants appear to have higher levels of English fluency, education, and income (relative to natives) than do U.S. female immigrants. This skill deficit for U.S. female immigrants arises in large part because the United States receives a much larger share of immigrants from Latin America than do the other two countries. However, even among women originating outside Latin America, the proportion of foreign-born women in the United States who are fluent in English is much lower than among foreign-born women in Australia. Furthermore, immigrant/native education gaps are reduced but not eliminated by the exclusion of Latin American women from the analysis. In contrast, other evidence for men suggests that the gap in observed skills among male immigrants to the United States is completely eliminated when Latin American immigrants are excluded from the estimation sample (Borjas, 1993; Antecol, et al., 2001). The importance of national origin and the general consistency in the results for men (who are routinely subjected to the selection criteria of various immigration programs) and women (who are not) suggests that many factors other than immigration policy per se are at work in producing skill variation among these three immigration streams.
Keywords: 330